The Question is not “If to Localise?” but Rather “How to Localise?”: Perspectives from Irish Humanitarian INGOs - Gibbons, Pat; Otieku-Boadu, Cyril (Frontiers in Political Science, 2021)
The localisation agenda has found a new impetus following the COVID 19 pandemic. International NGOs increasingly accept the inevitability of localisation and few would argue against its conceptual benefits. However, the challenge to operationalise localisation exposes fundamental differences in the INGO community. While all humanitarian INGOs share a common set of humanitarian principles, these principles sit alongside other principles and values that shape the fundamental strategic management processes of these organisations. This study of Irish humanitarian NGOs shows that organisations are at different stages in fully institutionalising localisation. Most of these organisations depend on a common resource pool that in turn has considerable influence over the speed of localisation. The big messages emanating from this study are that localisation is not without risk which needs to be shared by all stakeholders and many organisations will need to augment their strategic management processes to fully embrace localisation.